RFID Based Fuel Payment System Design - Komansilan, Trudi; Chirtoffel, Michaell; Duke , Abdul Fajar; Omega, Marcelliano (International Journal of Information Technology and Education, 2022)
In the current era, technological developments are so rapid and there are not a few technologies that offer a variety of advantages, both in terms of the functionality of the technology or its effectiveness, which of course all aim to make it easier for users, namely humans themselves. One example is RFID. This system has been widely applied both to identify an item, as a security system, and a toll payment system as well as arriving at an educational institution. The purpose of this research is to design a BBM payment system at gas stations based on RFID. Of course this aims to overcome some of the problems that occur and develop in the location. In this system, a card will be used as an RFID tag which will later be used as a payment medium that will be detected on a device that already attached to the refueling machine. This research uses the sprint design method which is the development of the design thinking method. That way by using the sprint design method in which there are stages of approach to the user, it is hoped that they can find the main problems faced and be able to design a solution that is able to overcome the existing problems.